Economic Influences on Plantation Sector Stock Prices in Malaysia: A Quantile Regression Approach - Ken, Wong Vui; Pinjaman, Saizal (Business and Economic Research, 2024)
This study aims to examine the relationship between microeconomic, sentiment, and macroeconomic variables across three quantiles (q25, q50, and q75) of stock prices in the Malaysian plantation sector. This study used Earnings per share (EPS) and return on equity (ROE) as the proxy for microeconomic variables, consumer sentiment index (CSI), and business condition index (BCI) as the proxy for sentiment variables, while inflation (INF which proxy from consumer price index) and exchange rate (ER, RM/USD) as the proxy for macroeconomic variables. Using a panel dataset covering 32 listed companies in plantation sector from 2008Q3 to 2023Q3. Result of quantile regression indicates that EPS, BCI, INF have a consistently positive and statistically significant relationship with stock prices across all quantiles. ROE has a mixed impact, with a positive relationship at the 25th and 50th quantile, but with a negative relationship at the 75th quantile. Furthermore, CSI and ER have a consistently negative and statistically significant relationship with stock prices across all quantiles.